Dengue virologically and serologically confirmed in Cali - Astudillo Cuero, Jair; Restrepo de Mesa, María Teresa; Tafur Calderón, Luis Alberto (Colombia Medica, 1989)
Blood samples were analyzed for dengue virus in 19 patients of Centro de Atención Básica, La Selva, Instituto de Seguros Sociales, and 44 people who asked for virological examinations for dengue at the Virus Laboratory of Microbiology Department, Universidad del Valle. Twenty cases had classic symptoms of the illness and positive virus culture, 18 dengue for virus type 1 and 2 for virus type 2. Nine others had classic symptoms and seroconversion titers suggestive of dengue. Primary immunologic response in 16 and secondary 6. In 7 patients, immunologic response could not be identified. Ten cases had minor hemorrhagic phenomena. Dengue hemorrhagic fever or dengue shock syndrome cases were not observed. The simultaneous presence of infections by virus types 1 and 2 indicates an increased risk of hemorrhagic dengue. Aedes aegypti control by sanitary authorities is urgent in Cali.